2011
DOI: 10.4314/ajtcam.v8i2.63202
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Cytotoxicity Screening of Five Medicinal Plants Used by Traditional African Health Practitioners in the Nelson Mandela Metropole, South Africa

Abstract: Diabetes mellitus is a growing problem in South Africa and of concern to traditional African health practitioners in the Nelson Mandela Metropole, because they experience a high incidence of diabetic cases in their practices. A collaborative research project with these practitioners focused on the screening of Bulbine frutescens, Ornithogalum longibracteatum, Ruta graveolens, Tarchonanthus camphoratus and Tulbaghia violacea for antidiabetic and cytotoxic potential. In vitro glucose utilisation assays with Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…An infusion of fresh leaves in a cup of boiling water is taken for coughs, arthritis and colds [46]. A report by van Huyssteen et al [47] showed that whole plant aqueous extract of B. frutescens increased glucose uptake in Chang liver cells. This effect was greater than the standard positive control, metformin, used in the study.…”
Section: Bulbine Frutescens (L) Willdmentioning
confidence: 99%
“…An infusion of fresh leaves in a cup of boiling water is taken for coughs, arthritis and colds [46]. A report by van Huyssteen et al [47] showed that whole plant aqueous extract of B. frutescens increased glucose uptake in Chang liver cells. This effect was greater than the standard positive control, metformin, used in the study.…”
Section: Bulbine Frutescens (L) Willdmentioning
confidence: 99%
“…Another of the mechanisms for managing hyperglycaemia is via improving insulin sensitisation to enhance glucose uptake ( VAN DE VENTER et al, 2008). Extract of Vernonia amygdalina leaves has been shown to significantly improve glucose utilization in C2C12 muscle cells (ERASTO et al, 2009), corroborating the ethnomedicinal antidiabetic use of the plant.…”
Section: Glucose Uptake Enhancement Activitymentioning
confidence: 87%
“…Extract of Vernonia amygdalina leaves has been shown to significantly improve glucose utilization in C2C12 muscle cells (ERASTO et al, 2009), corroborating the ethnomedicinal antidiabetic use of the plant. Others include extracts of Euclea undulata, Schkuhria pinnata (DEUTSCHLÄNDER et al, 2009), Tanacetum nubigenum (KHAN et al, 2018), Ruta graveolens and Tulbaghia violacea, among others ( VAN HUYSSTEEN et al, 2011).…”
Section: Glucose Uptake Enhancement Activitymentioning
confidence: 99%
See 2 more Smart Citations